Improvement of Arabic Speaking Skills Through the Total Physical Response Learning Method at The State Islamic Junior High School - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: The goal of this study is to find out how much students' ability to speak Arabic (maharah kalam) improves when they use the Total Physical Response (TPR) method to learn Arabic at class VII-A Islamic Junior High School or MTsN (4) in Jombang, Indonesia, as well as what factors help and hurt their progress. Design/ methods/approach: This study used spiral system classroom action research. This research followed the Hopkins model research design, starting with preliminary acts, then planning, action, observation, and reflection. The research cycled twice. Cycle II improved on cycle I's incomplete evaluation results. Cycle I reflection determined Cycle II improvements. This study yielded qualitative and quantitative data. Quantitative data comes from teacher observations, student interviews, and field notes. Student activities and post-learning evaluations provide quantitative data. The data came from students of class VII-A Islamic Junior High School (4) in Jombang, Indonesia. This study used observation, testing, and field notes. Data analysis completed a study. Interviews, field notes, student evaluations, and teacher observations were assessed. Instructor observations, interviews, and field notes shaped conclusions. Data analyzed student evaluation and activities. Findings: The results showed (1) With the TPR learning method, the score of the test results in the first stage at the end of learning maharah kalam Arabic averaged 60.98%, which is so good. After being given directions back in the second stage, it reached an average of 72 % or with good criteria; (2) The supporting factors that influence speaking activities are language (linguistic) and non-linguistic (non-linguistic), while the inhibiting factors are more dominant to the lack of mastery of mufradat